The secret battalion : an examination of the communist attitude to the Labour Party - Laski, Harold J. (London : Labour Party, 1946)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: Labour Party; Communistische Partij van Groot-Brittannië.